2018
DOI: 10.1111/jdv.15228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a non‐ablative, fractional 1565 nm laser for the improvement of striae distensae albae

Abstract: The use of a fractional non-ablative 1565 nm laser represents a safe approach for the treatment of SD albae. Clinically observed improvements were supported by significant data from objective measurements. The results achieved at 1-month FU represented at 6-month FU, showing stable clinical improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In our present study series, we found an apparent reduction in the striae depth and width in rendered 3D images after three treatment sessions on both sides. Very similar results were observed by Guertler et al . in their previous study using a PRIMOS clinical image system and by Harmelin et al .…”
Section: Discussionsupporting
confidence: 90%
“…In our present study series, we found an apparent reduction in the striae depth and width in rendered 3D images after three treatment sessions on both sides. Very similar results were observed by Guertler et al . in their previous study using a PRIMOS clinical image system and by Harmelin et al .…”
Section: Discussionsupporting
confidence: 90%
“…A total of 50 keloids were objectively measured using PRIMOS ®pico , a three‐dimensional, high‐resolution, non‐invasive clinical imaging device (Lite Device, GF Messtechnik GmbH, Teltow, Germany). PRIMOS ®pico has been successfully used to analyse different kinds of pathologic scarring, such as hypertrophic burn scars, 12 self‐harm scars 13 and striae distensae albae, 14 and has become a standard for scar imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Scores ranged from 0 (no impact) to 30 (maximum impact). Validated bands gave meaning to the scores as follows: 0‐1 = no effect on patients’ life; 2‐5 = small effect; 6‐10 = moderate effect; 11‐20 = very large effect; 21‐30 = extremely large effect 20 …”
Section: Methodsmentioning
confidence: 99%
“…Validated bands gave meaning to the scores as follows: 0-1 = no effect on patients' life; 2-5 = small effect; 6-10 = moderate effect; 11-20 = very large effect; 21-30 = extremely large effect. 20 Forty-four out of 60 patients (73%) of the cohort completed the study. 34 of 50 patients within the intervention group and all patients (10/10) within the control group were followed up until V2.…”
Section: Questionnairesmentioning
confidence: 99%